The INTERSECTION OF SOCIAL MEDIA LEARNING AND ENTREPRENEURIAL ORIENTATION: EFFECTS ON ACADEMIC OUTCOMES FOR GEN Z HIGHER EDUCATION STUDENTS - Rinaldi, Banu; Herlina, Maria Grace; Ikhsan, Ridho Bramulya (Journal of Business Studies and Management Review, 2024)
This study examines the influence of social media learning and entrepreneurial orientation on the academic performance of Generation Z in higher education institutions. Conducted in Greater Jakarta from February to June 2023. It involved 216 gen Z participants. The research utilised Rasch Model Analysis and Chi-Square Analysis for data examination. The research results revealed that students proficient in entrepreneurial orientation and social media learning had better GPAs, although social media learning alone did not significantly impact academic performance. The study underscores the importance of combining entrepreneurial orientation with social media learning to enhance academic performance in Generation Z students. It highlights the need for further research, considering the limited geographical scope and the lack of data on specific educational social media platforms. This research contributes to understanding how to effectively use social media and entrepreneurial skills to improve academic outcomes in higher education settings.